Historico-Cultural Trauma in Postcolonial Nigeria: A Critical Analysis of Half of a Yellow Sun - Neupane, Surya Prasad; Neupane, Bharat Prasad; Luitel, Peshal (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
The present article has critically analyzed the consequences of ‘communal violence’ resulting from the construction of communal identities in postcolonial Nigeria by projecting the historical legacy of colonialism into the fabric of the nation's identity, leading to the Nigerian Civil War, centered on the novel Half of a Yellow Sun looking through the lens of trauma and eventually attempting to bridge the gap by drawing the concept of Edward Said’s Critical Humanism (2004) along with Avishai Margalit’s idea of memory and morality. Major Nigerian tribes’ – the Igbos and the Hausas – construction of ethno-religious communities caused the Civil War in Nigeria, which created havoc in the society stemming from hatred and the superiority complex, a legacy of colonialism which is not only evident in the search for ‘collective identity’ in the name of ethnicity but also the daily lives of citizens, from peasants to intellectuals, i.e. Ugwu to Odenigbo. The colonial legacy in postcolonial situations is deciphered in multiple ways. However, the study has mainly centered on historico-cultural trauma by explicitly linking colonialism and the ethnic and political strife of the new nation (Biafra). Finally, it traces the significance of “thin morality" and the essence of “ethics of coexistence" to confront and overcome the deep-seated historico-cultural trauma in postcolonial Nigeria, based on the evidence from the narrative.